2021
DOI: 10.1186/s41606-021-00064-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep during infancy, inhibitory control and working memory in toddlers: findings from the FinnBrain cohort study

Abstract: Background Sleep difficulties are associated with impaired executive functions (EFs) in school-aged children. However, much less is known about how sleep during infancy relates to EF in infants and toddlers. The aim of this study was to investigate whether parent-reported sleep patterns at 6 and 12 months were associated with their inhibitory control (IC) and working memory (WM) performances at 30 months. Methods This study included children whose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In contrast, Morales‐Munoz et al. ( 2021 ) described an inverted U‐shaped association between the proportion of day to night sleep at 1 year of age and inhibitory control 2 years later, which can only be explained by appealing to both the sleep deficit and the maturational models of sleep. In support of the maturational view, Lam et al.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, Morales‐Munoz et al. ( 2021 ) described an inverted U‐shaped association between the proportion of day to night sleep at 1 year of age and inhibitory control 2 years later, which can only be explained by appealing to both the sleep deficit and the maturational models of sleep. In support of the maturational view, Lam et al.…”
Section: Introductionmentioning
confidence: 93%
“…Because sleep is highly dynamic, trajectories differ between infants, and long-lasting sleep problems may have more severe consequences than more temporally isolated sleep problems ( Smithson et al, 2018 ), we chose to characterize the trajectories of sleep across the first year of life. Most studies on infant sleep and development have only assessed sleep once or twice over the course of the first year ( Bernier et al, 2010 , 2013 ; Friedrich et al, 2017 ; Gibson et al, 2012 ; Mäkelä et al, 2020 ; Morales-Muñoz et al, 2020 ; Scher, 2005 ) and thus provide little insight into how changes in sleep duration over time affect development. One study with more frequent sleep assessments has shown that infants may start with similar sleep durations but may have different developmental trajectories over the following months ( Smithson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%